Effect of waviness on thermal-flow characteristics in an inclined trapezoidal cavity filled with nano-encapsulated phase change material and water - Saleh, Habibis; Jelita, Marhama; Md Arifin, Norihan; Hashim, Ishak (Taylor & Francis, 2023)
This study examines the free convection in an inclined trapezoidal enclosure generated by a temperature difference between a flat cold wall and a wavy hot wall. The trapezoidal enclosure is filled with hybrid nanofluids. This new type of fluid consists of nano-encapsulated phase-change material (NEPCM) suspended in the base fluid. The NEPCM utilizes polyurethane as the cover with n-nonadecane as the core. The mathematical model is expressed in terms of partial differential equations and numerically solved using the finite element method. Parametric studies are used to analyse the effects of the inclination angle, NEPCM volume fraction, sloping wall angle, number of corrugation and the Rayleigh number. It is found that the extracted energy from the charging process is optimal for moderate values of the fusion temperature and undulation number at a high value of the NEPCM volume fraction.